2014
DOI: 10.3389/fncom.2014.00065
|View full text |Cite
|
Sign up to set email alerts
|

Compensating for thalamocortical synaptic loss in Alzheimer's disease

Abstract: The study presents a thalamocortical network model which oscillates within the alpha frequency band (8–13 Hz) as recorded in the wakeful relaxed state with closed eyes to study the neural causes of abnormal oscillatory activity in Alzheimer's disease (AD). Incorporated within the model are various types of cortical excitatory and inhibitory neurons, recurrently connected to thalamic and reticular thalamic regions with the ratios and distances derived from the mammalian thalamocortical system. The model is util… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
30
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 75 publications
0
30
0
2
Order By: Relevance
“…Significant evidence suggests that thalamo-cortical circuitry underlie the generation and modulation of alpha and theta rhythms and that average power is attenuated in these frequency bands for MCI and AD subjects (Jeong, 2004 ; Koenig et al, 2005 ; Jelles et al, 2008 ; Park et al, 2008 ). Several recent modeling studies have proposed a candidate mechanism citing impairment to thalamic reticular fibers in MCI and AD as the source of the dysfunction (Bhattacharya et al, 2011 , 2013 ; Li et al, 2011 ; Abuhassan et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Significant evidence suggests that thalamo-cortical circuitry underlie the generation and modulation of alpha and theta rhythms and that average power is attenuated in these frequency bands for MCI and AD subjects (Jeong, 2004 ; Koenig et al, 2005 ; Jelles et al, 2008 ; Park et al, 2008 ). Several recent modeling studies have proposed a candidate mechanism citing impairment to thalamic reticular fibers in MCI and AD as the source of the dysfunction (Bhattacharya et al, 2011 , 2013 ; Li et al, 2011 ; Abuhassan et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown a strong correlation between abnormal synchronization and brain disorders including epilepsy, Parkinson's disease, Alzheimer's disease, and schizophrenia. Studying the effects of channel noise on synchronization provides a mathematical framework towards understanding how neurons regulate synchronization in the presence of noise [59][60][61].…”
Section: Discussionmentioning
confidence: 99%
“…Neural systems could exhibit rhythmic oscillations, which are a type of synchronous state. Synchronization in neural systems is thought to be important for processing of sensory information and motor function [ 1 ], but the occurrence of synchronization in some specific areas of the brain may also be associated with some diseases, such as the epilepsy and Parkinson's disease [ 2 ]. Because of the importance of synchronization in neural systems, it has been studied for a long time from many aspects in neuroscience research [ 3 7 ].…”
Section: Introductionmentioning
confidence: 99%